GPR101 Mutations are not a Frequent Cause of Congenital Isolated Growth Hormone Deficiency - Castinetti, F; Daly, A F; Stratakis, C A; Caberg, J-H; Castermans, E; Trivellin, G; Rostomyan, L; Saveanu, A; Jullien, N; Reynaud, R; Barlier, A; Bours, V; et al. (Hormone and metabolic research, 2016)
Patients with Xq26.3 microduplication present with X-linked acrogigantism (X-LAG) syndrome, an early-childhood form of gigantism due to marked growth hormone (GH) hypersecretion from mixed GH-PRL adenomas and hyperplasia. The microduplication includes GPR101, which is upregulated in patients' tumor tissue. The GPR101 gene codes for an orphan G protein coupled receptor that is normally highly expressed in the hypothalamus. Our aim was to determine whether GPR101 loss of function mutations or deletions could be involved in patients with congenital isolated GH deficiency (GHD). Taking advantage of the cohort of patients from the GENHYPOPIT network, we studied 41 patients with unexplained isolated GHD. All patients had Sanger sequencing of the GPR101 gene and array comparative genome hybridization (aCGH) to look for deletions. Functional studies (cell culture with GH secretion measurements, cAMP response) were performed. One novel GPR101 variant, c.589 G>T (p.V197L), was seen in the heterozygous state in a patient with isolated GHD. In silico analysis suggested that this variant could be deleterious. Functional studies did not show any significant difference in comparison with wild type for GH secretion and cAMP response. No truncating, frameshift, or small insertion-deletion (indel) GPR101 mutations were seen in the 41 patients. No deletion or other copy number variation at chromosome Xq26.3 was found on aCGH. We found a novel GPR101 variant of unknown significance, in a patient with isolated GH deficiency. Our study did not identify GPR101 abnormalities as a frequent cause of GH deficiency.